Soil ecosystem changes by vegetation on old-field sites over five decades in the Brazilian Atlantic forest - Ortiz D.C. (2022)
© 2021, Northeast Forestry University.Vegetation types alter soil ecosystems by changing soil fauna community activities and soil physical–chemical properties. However, it is unclear how tree species (natural forest, native and exotic tree plantations) promote changes in the soil ecosystem, and if these changes alter functional groups of soil fauna and ecosystem services. To determine the effects of five decades of old-field vegetation on soil ecosystems in the Brazilian Atlantic Forest, field sampling of three ecosystems (exotic tree species Pinus elliottii Engelm. plantation, endangered tree species Araucaria angustifolia (Bertol.) Kuntze plantation, and a natural ecosystem) were carried out, as well using bait-lamina tests and bioassays with collembolans, earthworms and seeds of Lactuca sativa L. Field sampling evaluated the soil fauna community and soil physical–chemical properties. The bait-lamina test in situ was carried out for 14-days to determine fauna feeding activity, and the bioassays evaluated the reproduction of Folsomia candida, the avoidance of Eisenia andrei, and germination of L. sativa in the soil from each ecosystem. The results are: (1) vegetation type altered the soil fauna community composition; (2) soil fauna feeding was reduced in the plantations compared to the natural ecosystem; (3) a physical barrier was created by recalcitrant litter that compromised fauna community structure and seed bank germination in situ; and, (4) changes in soil physical–chemical properties promoted decomposers.